1956
DOI: 10.3402/tellusa.v8i3.9010
|View full text |Cite
|
Sign up to set email alerts
|

A Series Solution for the Barotropic Vorticity Equation and its Application in the Study of Atmospheric Vortices

Abstract: A method to obtain a series solution for the barotropic non-divergent, vorticity equation is given and is applied to the case of a vortex.A formula that gives the development of a symmetrical vortex as a function of radius, maximum velocity and latitude is obtained. A numerical example is worked out.The convergence of the series solution for the general case is discussed and shown to depend on the scale of motion to be forecast and conclusions are drawn regarding time-steps used in a forecast and the smoothing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 2 publications
1
53
0
Order By: Relevance
“…(11); see Adem (1956) for a similar expansion. It is clear that a 0;0 ðyÞ ¼ ÀxðyÞ, so that starting from the zeroth-order approximation it is possible to find the first-order coefficients, which, in turn, yield the second-order approximation coefficients, and so on.…”
Section: A New Approximation For Topographic Rossby Waves In a Channelmentioning
confidence: 78%
“…(11); see Adem (1956) for a similar expansion. It is clear that a 0;0 ðyÞ ¼ ÀxðyÞ, so that starting from the zeroth-order approximation it is possible to find the first-order coefficients, which, in turn, yield the second-order approximation coefficients, and so on.…”
Section: A New Approximation For Topographic Rossby Waves In a Channelmentioning
confidence: 78%
“…The subject of coupling of monopolar vortices to waves on a ␤-plane has been subject of an extensive branch of the geophysical fluid dynamics literature. 22,[39][40][41][42][43][44][45][46][47][48][49] It has been found that with increasing intensity of the vortex, the dispersion decay of the vortex slows down substantially 20,50-52 and perturbation analysis based solutions describing stationary, i.e., nonradiating, anticyclonic monopolar vortices on the ␤-plane have been published. 26 The dynamics of the structure of the vortices on the rotating sphere lies outside the scope of the work presented here.…”
Section: Remarks On the Dynamics Of The Local Vortex Structure Andmentioning
confidence: 99%
“…The latter was first postulated by Rossby (1948) who noted that a vortex causes a deflection of the mean PV field and thus wil tend to migrate meridionally to reduce this deflection. Adem (1956) showed by means of a Taylor expansion in time that a cyclonic vortex drifts initially to the northwest.…”
Section: Previous Workmentioning
confidence: 99%